Practice of Nature Conservation in Intensive Forestry - Kaushik, R. C. (Indian Forester, 1969)
It is emphasised that nature conservation and forestry are inseparable. Forestry science developed out of need to preserve forests, the destruction of which earlier lead, Inter alia, consequent to deficient wood supplies and calamities resulting from too much water at times and too little when needed the most. Forestry, thus evolved itself as an organized profession for a concerted social action to conserve forest resources for supplies of goods and services to mankind in perpetuity. This,in fact, was the foundation of the concept of nature conservation also. Therefore, a sound uderstanding of natural equilibrium in a forest area and the judicious manipulation of the natural balance to obtain the needed produce and protection in perpetuity without jeopardising the productivity of the site, formed the very basis of scientific forestry right from its beginning over two centuries ago. Since its inception, forestry practice has squarely rested on the knowledge of nature and the science of forestry has consistently penetrated deeper in to the secrets of,nature to understand the phenomenon of growth in forest vegetation and its variation on different sites under different conditions. Later on, consequent to increased demand on forest produce due to increasing population coupled with overall economic development, the need for increasing productivity from a limited forest area became obvious in many parts of the world, particularly in regions deficient in natural forests. India is no exception to this development but the fundamental approach of the forester to maintain and improve the site to get increasing yields and indirect benefits has remained unchanged and it is indeed the mainstay of the intensive forestry practice involving not only heavy financial investment but also much higher order of professional competence, the yard-stick for which continues to be the conservation of the locality and the improvement of the site. Consistent with the concept of the multiple use of forests, which includes the preservation and conservation of both fauna and flora and the provision of the goods and services necessary for the welfare of a country, it is but natural that the practice of intensive forestry takes care of all the benefits accruing from forests-productive, protective and bio-aesthetic. This important aspect is adequately ensured in the practice of intensive forestry in India. Further, plantation forestry can provide adequate economic returns only on most productive sites. Therefore the bulk of the area continues to be maintained as natural forest since highly productive sites inside forest areas are very limited as out of 75 million ha of forests in the country, the plantations cover an area of about 1.3 million ha which is barely 1.7% of the total forest area. Much more needs to be done in this respect realising the fact that India has over 15% of the world’s population on only 2.5% of the world’s area with only 1.8% of the world’s forest carrying an average growing stock of only 32 m3 per ha against the world’s average of 110 m3 per ha.